2016
DOI: 10.1186/s13019-016-0449-4
|View full text |Cite
|
Sign up to set email alerts
|

Successful fast track protocol implementation for patients undergoing transapical transcatheter aortic valve implantation

Abstract: BackgroundThe aim of the current study is to report our experience with fast-track treatment of patients undergoing transapical transcatheter aortic valve implantation (TA-TAVI) and to determine perioperative predictors for fast-track protocol failure.MethodsBeing one of the pioneering centers to start performing TA-TAVI back in 2005, we routinely included patients undergoing this procedure into our fast-track management program since 2008. Between January 2008 and June 2013, 207 consecutive high-risk patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…It is also related to preoperative anxiety, pain, preparation, risk factors and the patient's knowledge and expectations of the surgical process (Ayyadhah Alanazi, 2014; Husted, 2012; Johansson Stark et al, 2014; McClurkin & Smith, 2016; Pettersson et al, 2017). Two papers analyse fast‐track surgical procedures and conclude that abbreviating the perioperative period and facilitating prompt discharge significantly enhance clinical results (Dries, 2018; Papadopoulos et al, 2016). These findings corroborate Vogl et al, (2015), who suggested that a shorter hospital stay was not associated with worse health outcomes after 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also related to preoperative anxiety, pain, preparation, risk factors and the patient's knowledge and expectations of the surgical process (Ayyadhah Alanazi, 2014; Husted, 2012; Johansson Stark et al, 2014; McClurkin & Smith, 2016; Pettersson et al, 2017). Two papers analyse fast‐track surgical procedures and conclude that abbreviating the perioperative period and facilitating prompt discharge significantly enhance clinical results (Dries, 2018; Papadopoulos et al, 2016). These findings corroborate Vogl et al, (2015), who suggested that a shorter hospital stay was not associated with worse health outcomes after 6 months.…”
Section: Resultsmentioning
confidence: 99%
“…Among the articles reviewed, the two most frequent years of publication were 2018 (Brown et al, 2018;Dries, 2018;Wyatt et al, 2018) and 2020 (Derseh et al, 2020;da Silva Schulz et al, 2020;Vogl et al, 2015) (n = 3), followed by 2012 (Husted, 2012;Johansson Stark et al, 2014), 2015 (Crump et al, 2015;Liederbach et al, 2015) (n = 2), 2011 (Papadopoulos et al, 2016), 2014(Ayyadhah Alanazi, 2014(McClurkin & Smith, 2016, 2017 (Pettersson et al, 2017(de Lorenzo-Pinto et al, 2019. None of these articles were published in 2013 or 2021 (Figure 2).…”
Section: Characteristics Of the Articles Reviewedmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the minimally invasive nature of the TAVI approach, patients undergoing TAVI represent a suitable cohort for early recovery [ 6 ]. However, transapical-TAVI (TA-TAVI) procedures need sufficiently profound neuromuscular blockade (NMB) during surgery which improves surgical conditions by inhibiting skeletal muscle movements.…”
Section: Introductionmentioning
confidence: 99%